Surrogate surfaces: a contextual interpretive approach to the rock art of Uganda - Namono, Catherine (My University, 2010)
Abstract Rock art in Uganda is under-researched, and where research has been done the rock art was erroneously attributed to ‘Bushman-like’ people. This misattribution resulted in flawed interpretations. Uganda forms part of the geometric art zone that spreads across central Africa, including Angola, northern Mozambique, Zambia, Malawi and the Democratic Republic of Congo. Using a contextual interpretive approach, this thesis considers the meaning of the geometric rock art of Uganda. Arising from recording and analysis of geometric rock art sites in Uganda, a literature review and archival searches on oral traditions and interviews with heritage holders, the study attempts to sequence the art and tie identified patterns in the rock art to data from ethnography, oral tradition and archaeological sources. In this thesis, I consider the geometric rock art in Uganda to be made within a context of ritual. This study makes an empirical contribution by generating a comprehensive database of rock art in Uganda. Methodologically, this is the first time that a contextual approach is used to identify patterns and to interpret the rock art in Uganda. Interpretatively, this study generates new knowledge about the geometric rock art as well as information on related living heritage.